Making Sense of the Dollar: Exposing Dangerous Myths about Trade and Foreign Exchange - Chandler Marc (Bloomberg, 2009)
Has the greenback really lost its preeminent place in the world? Not according to currency expert Marc Chandler, who explains why so many are--wrongly--pessimistic about both the dollar and the U.S. economy.